Evaluación nutricional en escolares del primer grado de nivel primario del centro educativo mariano melgar, distrito el porvenir, 2009 - Pashco Morillas, Maritza Janet (2009)
The present study of investigation is oriented to EVALUATION NUTRICIONAL IN STUDENTS OF THE FIRST GRADE OF PRIMARY LEVEL OF THE EDUCATIVE CENTER MARIANO MELGAR, THE PORVENIR DISTRICT, 2009. Using the anthropometric Method, the data were grouped in comparative tables , determining the number of students of both sorts that present normal nutricional state, overweight, obesity, acute and chronic undernourishment. Where the following results were obtained: According to the relation Weight for the stature: of boys 42.85% (12) they presented a normal relation but with tendency of 17.14% (2) to the acute undernourishment degree and 7.14% (2) to the obesity; whereas 17.85% (5) suffer properly of obesity this. On the contrary between the girls, 25% (7) presented a normal relation; 3.57% (1) with tendency to the acute undernourishment degree 1 and similar percentage with respect to the obesity, whereas 14.28% (4) present obesity properly this. In relation to Talla for the age (Stature/Age), of the boys, 25% (7) present normality, 3.57% (1) tends to the chronic undernourishment degree 1; 35.72% (10) with chronic undernourishment degree 1 itself and 3.57% (1) tend to the chronic undernourishment degree 2. For the girls the normality relation was of 25% (7); 7.14% (2) tend to the chronic undernourishment degree 1 and 14.28% (4) presented chronic undernourishment degree 1. According to the Index of Corporal Mass (IMC), 17.75% (5 boys) have overweight and only 3 girls (10.71%) presented he himself picture. Of the obtained results one concludes that: In the students of the first degree of primary level of the educative Center Mariano Melgar of the Porvenir district the , predominates the followed state of normal nutrition of the chronic and acute undernourishment, finally in smaller proportion the obesity